Artificial Intelligence in Oral Cancer Diagnosis and Prognosis: A Review (Academia Journal of Medicine, 2026)
Oral cancer, predominantly oral squamous cell carcinoma (OSCC), remains a major global  health burden with high morbidity and mortality rates due to late diagnosis and limited  prognostic accuracy. Artificial Intelligence (AI), encompassing machine learning (ML) and  deep learning (DL), has emerged as a transformative tool in healthcare, offering enhanced  diagnostic precision, early detection, and prognostic prediction. AI-based systems analyze  large datasets including clinical images, histopathological slides, radiographic scans,  and molecular profiles to assist clinicians in decision-making. This review explores the  applications of AI in oral cancer diagnosis and prognosis, highlighting recent advancements,  advantages, limitations, and future perspectives.
Keywords: Artificial Intelligence, Oral Cancer, OSCC, Machine Learning, Deep Learning, Diagnosis, Prognosis